Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the distance between the points [tex]\((1, -2)\)[/tex] and [tex]\((2, 4)\)[/tex], we use the distance formula, which is given by:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
First, identify the coordinates [tex]\((x_1, y_1) = (1, -2)\)[/tex] and [tex]\((x_2, y_2) = (2, 4)\)[/tex].
Now, compute the differences in the [tex]\(x\)[/tex]-coordinates and [tex]\(y\)[/tex]-coordinates:
[tex]\[ (x_2 - x_1) = 2 - 1 = 1 \][/tex]
[tex]\[ (y_2 - y_1) = 4 - (-2) = 6 \][/tex]
Next, square these differences:
[tex]\[ (x_2 - x_1)^2 = 1^2 = 1 \][/tex]
[tex]\[ (y_2 - y_1)^2 = 6^2 = 36 \][/tex]
Now, sum the squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 1 + 36 = 37 \][/tex]
Finally, take the square root of this sum to find the distance:
[tex]\[ \text{Distance} = \sqrt{37} \approx 6.082762530298219 \][/tex]
Given the expressions in the options:
- Option A. [tex]\((1+2)^2 + (2-4)^2\)[/tex] is incorrect because it incorrectly sums [tex]\(x\)[/tex]-coordinates and does not use the correct difference.
- Option C. [tex]\((1 - 2)^2 + (-2 - 4)^2\)[/tex] misses the square root and thus does not give the distance.
- Option D. [tex]\(\sqrt{(1+2)^2 + (2 - 4)^2}\)[/tex] incorrectly sums [tex]\(x\)[/tex] coordinates.
The correct option is B, which matches the distance formula:
[tex]\[ \sqrt{(1 - 2)^2 + (-2 - 4)^2} \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\sqrt{(1 - 2)^2 + (-2 - 4)^2}} \][/tex]
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
First, identify the coordinates [tex]\((x_1, y_1) = (1, -2)\)[/tex] and [tex]\((x_2, y_2) = (2, 4)\)[/tex].
Now, compute the differences in the [tex]\(x\)[/tex]-coordinates and [tex]\(y\)[/tex]-coordinates:
[tex]\[ (x_2 - x_1) = 2 - 1 = 1 \][/tex]
[tex]\[ (y_2 - y_1) = 4 - (-2) = 6 \][/tex]
Next, square these differences:
[tex]\[ (x_2 - x_1)^2 = 1^2 = 1 \][/tex]
[tex]\[ (y_2 - y_1)^2 = 6^2 = 36 \][/tex]
Now, sum the squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 1 + 36 = 37 \][/tex]
Finally, take the square root of this sum to find the distance:
[tex]\[ \text{Distance} = \sqrt{37} \approx 6.082762530298219 \][/tex]
Given the expressions in the options:
- Option A. [tex]\((1+2)^2 + (2-4)^2\)[/tex] is incorrect because it incorrectly sums [tex]\(x\)[/tex]-coordinates and does not use the correct difference.
- Option C. [tex]\((1 - 2)^2 + (-2 - 4)^2\)[/tex] misses the square root and thus does not give the distance.
- Option D. [tex]\(\sqrt{(1+2)^2 + (2 - 4)^2}\)[/tex] incorrectly sums [tex]\(x\)[/tex] coordinates.
The correct option is B, which matches the distance formula:
[tex]\[ \sqrt{(1 - 2)^2 + (-2 - 4)^2} \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\sqrt{(1 - 2)^2 + (-2 - 4)^2}} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.